Queerness is a Particular Liability: Feeling Rules in College and University LGBTQ Centers. Issue 3 (23rd February 2023) - Mandala, Chad R.; Ortiz, Stephanie M.
ABSTRACT: Organizational sociologists argue that informal and formal rules within workplaces function to increase employee productivity and effectiveness, but can also have negative emotional consequences. Feeling rules, which are the emotional norms that regulate interpersonal interactions within the workplace are not applied equally; white women and professionals of color are expected to display deference in the face of emotionally-charged experiences at work, while their counterparts are given more flexibility in how they could display anger or annoyance. Scholars note that feeling rules work to reproduce extant gendered and racial hierarchies when expectations regarding worker productivity, effectiveness and outcomes are restricted on the basis of social identities. Analyzing sixteen semi-structured interviews with LGBTQ Center staff, we demonstrate the feeling rules are organized around employees' ability to (1) (re)produce trauma in themselves during training sessions and (2) minimize students' and their own anger throughout the workday.